1996
DOI: 10.1103/physreve.53.r5592
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a contact surface driven by a nonuniform shock wave

Abstract: Stability of a uniform contact surface is investigated in the case when a nonuniform shock wave passes through the surface. The nonuniform shock is generated by a rippled piston that moves with constant velocity. The amplitude of the shock oscillates and decreases as it propagates. A uniform contact surface is found to be unstable after the nonuniform shock passes across it. The growth rate depends sensitively on the phase of the oscillating shock wave at the time when the shock hits the contact surface. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 6 publications
1
37
2
Order By: Relevance
“…Once a rippled shock is launched, a pressure perturbation is induced by lateral fluid motion behind the shock, and the pressure perturbation causes the ripple of the shock front to be reversed and subsequently oscillate, similar to the shockinterface interaction discussed before. However, compared with the rippled shock driven by a rippled rigid piston (dotted line in figure 7; Briscoe & Kovitz 1968;Ishizaki et al 1996), the amplitude of the shock surface ripple driven by laser ablation decays much faster than that driven by a rigid piston. The pressure perturbation increases the deformation of the ablation front monotonously.…”
Section: (E) Rm-like Instabilities and Ablative Rmimentioning
confidence: 96%
“…Once a rippled shock is launched, a pressure perturbation is induced by lateral fluid motion behind the shock, and the pressure perturbation causes the ripple of the shock front to be reversed and subsequently oscillate, similar to the shockinterface interaction discussed before. However, compared with the rippled shock driven by a rippled rigid piston (dotted line in figure 7; Briscoe & Kovitz 1968;Ishizaki et al 1996), the amplitude of the shock surface ripple driven by laser ablation decays much faster than that driven by a rigid piston. The pressure perturbation increases the deformation of the ablation front monotonously.…”
Section: (E) Rm-like Instabilities and Ablative Rmimentioning
confidence: 96%
“…The dependence of the growth rates on the shock phase was found to be similar even for different Atwood numbers. 9 We have shown that the contour of the vortex filament selforganization depends on the phase of the RT instability modes.…”
Section: Laser-induced Evolution Of Hypocycloidal Formation Of Vortexmentioning
confidence: 83%
“…Instability growth at the fuel-ablator interface can originate either from a local perturbation at this interface or from a perturbation that imprints from the ablation front [20][21][22][23][24][25][26]. These experiments address both scenarios.…”
mentioning
confidence: 99%